Redefining the Role of Langerhans Cells As Immune Regulators within the Skin - West, Heather C.; Bennett, Clare L. (Frontiers in Immunology, 2018)
Langerhans cells (LC) are a unique population of tissue-resident macrophages that form a network of cells across the epidermis of the skin, but which have the ability to migrate from the epidermis to draining lymph nodes. Their location at the skin barrier suggests a key role as immune sentinels. However, despite decades of research, the role of LC in skin immunity is unclear; ablation of LC results in neither fatal susceptibility to skin infection nor overt autoimmunity due to lack of immune regulation. Our understanding of immune processes has traditionally been centered on secondary lymphoid organs as sites of lymphocyte priming and differentiation, which is exemplified by LC, initially defined as a paradigm for tissue dendritic cells that migrate to draining lymph nodes on maturation. But, more recently, an awareness of the importance of the tissue environment in shaping effector immunity has emerged. In this mini-review we discuss whether our lack of understanding of LC function stems from our lymph node-centric view of these cells, and question whether a focus on LC as immune regulators in situ in the skin may reveal clearer answers about their function in cutaneous immunology.